Intoxication by the Berries of Coriaria Myritfolia - A Case Report - Mohsin Khan; Abdur Rehman; Faiza Khan; Naima Khan (Journal of Gandhara Medical and Dental Sciences)
T Coriaria Myritfolia is a shrub that grows 2-3 meters tall. The exact local name of the plant is unknown, but in Hindi, some species of Coriaria are called “Divi-Divi”. We report a case of intoxication following ingestion of fruits of  Coriaria Myritfolia. A 6-year-old boy, the previously healthy child, was brought to the pediatric emergency department after accidentally ingesting red berries from a tree growing wild in district Haripur. On inquiry, the parents of the child reported that after the ingestion of an unknown quantity of fruit, the child felt nauseated and vomited. We sought care from a local Physician who treated the outpatient as a case of food poisoning. The child didn’t get better and, after 4-6hr from the ingestion of berries, felt a generalised-tonic-clonic seizure with up rolling of the ball and incontinence. The parents immediately brought the child to a tertiary care hospital. Upon arrival at the hospital, the patient was somnolent with generalised hypotonia. The Prophylactic 10mg Diazepam (0.4mg/kg) is given per rectal. The peripheral intravenous line passed. Initial labs were not conclusive except for hypokalemia and metabolic acidosis. He was started on the prophylactic antiseizure elixir of Phenobarbital 5mg/kg/day and levetiracetam 400mg/ day. CT brain was normal. The patient was discharged after 3rd day of admission on anti-seizure medications. We concluded that the intoxication with the fruits of Coriaria Myritfolia could be managed successfully if the patient came to the hospital within 6-8 hours with anti-seizure medications.